STRATEGI KESANTUNAN SEBAGAI KOMPETENSI PRAGMATIK DALAM TINDAK TUTUR DIREKTIF BAHASA PRANCIS - Elvi Syahrin (BAHAS, 2008)
One of the important issues in pragmatics is politeness. In order to carry out successful communication, politeness seems to be an important device that serves to avoid unnecessary conflict between the speaker and a hearer. It means that the effort to be polite determines the choice of words and phases or linguistic variant in expressing the ideas or meaning in a given context. Brown & Levinson (1987) affirm that politeness is regarded as a universal phenomenon in language use. These linguists, well known by their theory of politeness strategies, divide four types of politeness strategies; Bald-on Record Strategy, Positive politeness strategy, Negative politeness strategy, and Off-record politeness strategy. Politeness strategies are ways chosen to convey the utterances as polite as possible. Based on Brown & Levinson’s theory of Politeness Strategy, this paper discuss about how politeness strategy is realized in French directives. In making directives, French seems to apply all the strategy. Emphasizing the importance of politeness in foreign language learning particularly in French, this paper provides not only theoretical conception about politeness strategy and its relevance in foreign language learning, but moreover it is aimed to inspire the reader, especially the language lecturers, to pay more attention to the application of politeness issues in classes and significantly in their researches. Kata Kunci: Strategi kesantunan, direktif, dan bahasa Prancis